Minat Global dalam Bidang Konservasi Gigi Sebelum dan Masa Pandemi COVID-19: Analisis Data Google Trends - Salmia Atika Desri; Hanim Khalida Zia; Widyawati Widyawati; Valendriyani Ningrum (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The COVID-19 pandemic situation has caused changes in needs and new challenges in dentistry services. Toothache often requires immediate treatment. The source of pain is generally caused by cavities that require conservative measures. The aim of this research is to analyze the changing global interest in dental conservation before and during the COVID-19 pandemic. This research used analytic observational method. The secondary data used came from Relative Search Volume (RSV) Google Trends, from all countries in the world that access search data through the Google database. This study used five keywords related to the field of tooth conservation, namely "tooth decay", dental veneers", "dental filling", "root canal treatment", "fracture tooth". Data from Google Trends was continued with statistical tests using the Wilcoxon test. The top searched topics related to tooth conservation are tooth decay, dental veneers, dental fillings, root canal treatment, fracture teeth. The results of Google Trends data analysis showed that there had been a significant change in interest in searching for information related to the field of dental conservation from before the pandemic to the pandemic worldwide with p-value <0.05 for all keywords. The decrease in keyword searches predicts concerns about dental treatment during a pandemic. Teledentistry is a program that can be used to prepare for effective remote dental services in the future.Keywords: global interest; Google Trends; toothache; tooth conservation; COVID-19 ABSTRAK Situasi pandemi COVID-19 menyebabkan perubahan kebutuhan dan tantangan baru dalam pelayanan kedokteran gigi. Rasa sakit gigi seringkali membutuhkan penanganan segera. Sumber rasa sakit pada umumnya diakibatkan oleh gigi berlubang yang memerlukan tindakan konservatif. Tujuan penelitian ini adalah menganalisis perubahan minat global dalam bidang konservasi gigi sebelum dan masa pandemi COVID-19. Penelitian ini menggunakan metode observasional analitik. Data sekunder yang digunakan bersumber dari Relative Search Volume (RSV) Google Trends, dari seluruh negara di dunia yang mengakses pencarian data melalui Google database. Penelitian ini menggunakan lima kata kunci yang terkait bidang konservasi gigi yakni “tooth decay”, dental veneers”, “dental filling”, “root canal treatment”, “fracture tooth”. Data dari Google Trends dilanjutkan dengan uji statistik menggunakan uji Wilcoxon. Topik teratas pencarian terkait konservasi gigi adalah tooth decay, dental veneers, dental filling, root canal treatment, fracture tooth. Hasil analisis data Google Trends menunjukkan adanya perubahan minat pencarian informasi terkait bidang konservasi gigi secara signifikan dari masa sebelum pandemi hingga masa pandemi di seluruh dunia dengan nilai p <0,05 pada semua kata kunci. Penurunan pencarian kata kunci tersebut memprediksi adanya kekhawatiran melakukan perawatan gigi pada masa pandemi. Teledentistry merupakan program yang dapat dikembangkan penggunaannya untuk mempersiapkan pelayanan kedokteran gigi jarak jauh yang efektif di masa depan.Kata kunci: minat global; Google Trend; sakit gigi; konservasi gigi; COVID-19